Effect of Cultivation Practices on the beta-Glucan Content of Agaricus subrufescens Basidiocarps - Zied, Diego Cunha; Pardo Gimenez, Arturo; Pardo Gonzalez, Jose Emilio; Dias, Eustaquio Souza; Carvalho, Maiara Andrade; Almeida Minhoni, Marli Teixeira de [UNESP] (Amer Chemical Soc, 2014)
The present work aimed to assess the effect of the following treatments on the medicinal potential (beta-glucan content) and agronomical performance (yield) of Agaricus subrufescens: five different fungal strains, three cultivation substrates (compost), four casing layers, and four cultivation environments. Two experiments were performed, and the results indicate that the greatest contribution to the variation in beta-glucan content was the strain (35.8%), followed by the casing layer (34.5%), the cultivation environment (15.7%), and the type of compost (9.9%). On the other hand the variation in yield was affected most by the cultivation environment (82.1%), followed by the strain (81.3%), casing layer (49.1%), and compost type (15.2%). These findings underscore the importance of developing a production protocol that employs specific cultivation practices for improving mushroom yield as well as beta-glucan content.
Keywords: almond mushroom; medicinal potential; strain; compost; yield